Pengajaran Bahasa Melayu sebagai Bahasa Asing kepada Pelajar dari Negara China : Perkongsian Pengalaman di Universiti Sains Malaysia - Baharudin, Mazlina; Md Radzi, Razalina (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Universiti Sains Malaysia (USM) is one of the earliest public university which was established in Malaysia after Universiti Malaya. USM is also the first university that has been given the Apex status in Malaysia which is the highest recognition and trust granted by the Ministry of Higher Education Malaysia to USM. USM has received students from different countries such as China, Libya, Sudan, Egypt, Nigeria, Indonesia, Thailand, Japan, Korea and other countries. However, this research focuses only on the international students from China who were registered as undergraduates in USM. This paper is based on the writer’s experiences in teaching Bahasa Malaysia III (LKM 300) as a university course that the students must pass as a requirement for international students to graduate. The main dimension of this research is to examine the effectiveness of teaching Malay language as a foreign language to international students (China) by using a teaching model that uses the Bahasa Malaysia III (LKM300) course module ) as determined by the School of Languages, Literacies and Translation. The research method used is full literature where the writers had referred to 43 international student’s final exam scripts that have taken the LKM300 course in the first semester of the 2012/2013 academic session. Their final exam result was taken for full analysis based on the different sections in the exam paper to be used as a source to conclude the research. This research is hoped to be able to provide an explanation of the effective results of the successful usage of the course module and students’ achievement.